Effectiveness of SIMPEG Use as A Personnel Data Center: (A Study of The Personnel and Human Resource Development Agency In Cirebon City) - Gayatri, Nabilla Putri; Imawan, Khaerudin; Rohida, Leni (Syntax Literate, 2026)
This study aims to evaluate the effectiveness of the use of the Personnel Information System (SIMPEG) as a personnel data center at the Cirebon City Personnel and Human Resources Development Agency (BKPSDM). Initial findings indicate that SIMPEG implementation has not been optimal, particularly in aspects of data integration, efficiency of administrative services, and the availability of accurate and up-to-date information. The study used a qualitative descriptive approach with data collection techniques through in-depth interviews, field observations, and documentation studies. The results show that SIMPEG has been able to store and manage personnel data centrally. However, there are still obstacles, including the lack of comprehensive system integration between applications, inconsistencies in data updates, and limitations in the number and competence of operators. Technology, human resources, and organizational support have been proven to influence the effectiveness of system implementation and the successful application of e-government principles. In terms of benefits, SIMPEG is considered to provide easy access, guarantee data security, and increase trust in personnel administration governance. However, data utilization for strategic decision-making is not optimal and still requires the development of more comprehensive analytical features. SIMPEG research has contributed to increasing the efficiency of personnel administration. However, technical improvements, strengthening system integration, modernizing technological infrastructure, and increasing human resource capacity are needed to ensure the system functions more effectively, responsively, and data-driven in supporting personnel policies